Medicinal and ornamental plant tissue culture in Brazil and worldwide: Researches and patents - Costa, Dora dos Santos; Direito, Ida Carolina Neves; Victório, Cristiane Pimentel (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
Different plant tissue culture techniques are used to produce medicinal and ornamental plants. Here, we quote such techniques, depending on the final product, and evaluate the trends of plant culture techniques used in Brazil and worldwide based on our research of patents and published papers from 2000 to 2018. We also present companies had work with plant tissue culture in Brazil. Although information is scarce, results show that patents for in vitro production of plants under controlled environmental conditions are expanding worldwide. While most Brazilian plant production is restricted to the domestic market, signs indicate that the international market could be expanding. Otherwise, the Chinese are the chief exporters in the production process of plantlets, which may be marketed as seedlings or used as biofactories for the pharmaceutical industry, for example. The main techniques based on plant tissue culture patents, are related to direct organogenesis, both for ornamental and medicinal tissue culture protocols. It is noteworthy that the number of patents related to tissue culture protocols for medicinal plants is higher than that for ornamental plants and that the number of published articles too, particularly those reporting on cultivation ofornamental and medicinal plants, far exceeds the number of patents related to plant tissue culture in general. Index terms: In vitro culture; plant market; plant biotechnology; intellectual property.